2019
DOI: 10.1002/cncr.32175
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported and clinician‐reported chemotherapy‐induced peripheral neuropathy in patients with early breast cancer: Current clinical practice

Abstract: BACKGROUND: In the current study, the authors investigated the incidence of moderate to severe chemotherapy-induced peripheral neuropathy (CIPN) for chemotherapy regimens commonly used in current clinical practice for the treatment of patients with early breast cancer. Patient-reported and clinician-assessed CIPN severity scores were compared, and risk factors for CIPN severity were identified. METHODS: Patients completed a Patient-Reported Symptom Monitoring form and oncologists completed a Common Terminology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 50 publications
3
52
0
3
Order By: Relevance
“…This is in accordance with Mooney, Berry, Whisenant, and Sjoberg (2017) who demonstrated that using a questionnaire may contribute to intensifying symptom care and improve quality of life among the patients (Mooney et al, 2017). However, the outcome may rely on the ability to narrow or close the gap between the patients' and the professionals' estimation and grading of symptoms, a gap which in other studies is articulated as a crucial problem (Molassiotis et al, 2019;Mooney et al, 2017;Nyrop et al, 2019).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This is in accordance with Mooney, Berry, Whisenant, and Sjoberg (2017) who demonstrated that using a questionnaire may contribute to intensifying symptom care and improve quality of life among the patients (Mooney et al, 2017). However, the outcome may rely on the ability to narrow or close the gap between the patients' and the professionals' estimation and grading of symptoms, a gap which in other studies is articulated as a crucial problem (Molassiotis et al, 2019;Mooney et al, 2017;Nyrop et al, 2019).…”
Section: Discussionsupporting
confidence: 75%
“…Multiple instruments have been developed to identify CIPN but no gold standard has been established, although it is common for physicians to use the scales of National Cancer Institute-Common Terminology Criteria Adverse Events (NCI-CTCAE) in their assessments of patients' adverse events. However, comparing a clinician-based grading system like the CTCAE scale with patient-reported outcome measures shows that professionals score patients' conditions lower than patient' themselves and thus identify fewer patients with CIPN (Molassiotis et al, 2019;Nyrop et al, 2019).…”
Section: Choice Of Instrumentmentioning
confidence: 99%
“…School, University of New South Wales, Sydney, NSW 2217, Australia. 7 Faculty of Medicine and Health, The University of Sydney, Sydney, NSW 2006, Australia. 8 Prince of Wales Clinical School, University of New South Wales, Sydney, NSW 2052, Australia.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…PROMs data may relate to one or multiple health-relevant domains including psychological and physical wellbeing, and be collected using a range of electronic and/or paper-based mediums [5]. Studies have identified differences between patient and clinician assessments of outcomes in oncology with regard to treatment side effects, numerous physical symptoms, as well as psychological issues, whereby oncologists only identified a small proportion of the total patients who were experiencing clinical anxiety and depression [6,7]. This discordance has not improved over the past two decades [6,7], supporting the need for patients' direct reports.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation